The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/17474930211047337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal impairment on short-term outcomes following endovascular thrombectomy for acute ischemic stroke: A systematic review and meta-analysis

Abstract: Background. The impact of renal impairment (RI) on the outcomes of patients with acute ischemic stroke (AIS) treated with endovascular thrombectomy (EVT) was relatively limited and contradictory. We performed a systematic review and meta-analysis to investigate this. Aims. We registered a protocol on September 2020 and searched MEDLINE, EMBASE, and Google Scholar accordingly. RI was defined as an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2. Predefined outcomes included functional indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…Recently, a systematic review and meta-analysis by Jeon et al 38 came to similar conclusions to our study. They searched MEDLINE, EMBASE, and Google Scholar on 11 September 2020, and their study contained some unpublished data obtained by contacting the corresponding authors of potential studies.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, a systematic review and meta-analysis by Jeon et al 38 came to similar conclusions to our study. They searched MEDLINE, EMBASE, and Google Scholar on 11 September 2020, and their study contained some unpublished data obtained by contacting the corresponding authors of potential studies.…”
Section: Discussionsupporting
confidence: 91%
“…21,22 Especially, despite randomized clinical trial can give some certainties to this gray area, previous trials could not answer this question because previous several legacy trials excluded the low-eGFR patients. 23 , In addition, most of the retrospective studies on the impact of low eGFR on the outcome after EVT included a small sample size and used a fixed reference for low eGFR (<30 or 60 mL/min per 1.73 m 2 ) without considering age-related or sex-related differences in eGFR. Furthermore, previous studies did not consider collateral status, occlusion site, or various comorbidities, including active cancer, which could affect the outcome after EVT.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Nationwide Inpatient Sample 2002–2009 revealed higher in-hospital mortality in dialysis-dependent patients than in non-dialysis patients treated with IV thrombolytics (22% vs 11%, P<0.0001) 23. In the modern EVT era, a meta-analysis showed that RD is associated with less functional independence (OR 0.59, 95% CI 0.45 to 0.77) and a higher mortality (OR 2.23, 95% CI 1.45 to 3.43) 24. The post hoc analysis of the DIRECT-MT trial revealed that patients with non-RD had a lower 90-day mRS than RD patients (common aOR 0.26, 95% CI 0.15 to 0.45) 25.…”
Section: Discussionmentioning
confidence: 99%